Translating interaction design guidelines for dyslexic children’s reading application - Aziz, Fakhrul Anuar; Husni, Husniza; Jamaludin, Zulikha (2013)
This paper presents a translation of interaction design (IxD) guidelines into a working prototype of dyslexic children’s reading application in Bahasa Melayu.The IxD guideline was specifically designed and developed with the motivation to help ease and reduce dyslexic children’s difficulties in reading.It is well established that dyslexics, due to dyslexia, have difficulties to learn, especially when it comes to reading that is caused by visual and auditory deficits.Unfortunately, reading applications, mostly in English language, are not designed specifically for dyslexics in terms of its form, content, and behaviour for such application.Hence, to help them read better, an IxD guidelines tailored specifically for dyslexic children is proposed.These guidelines are translated into prototype and show how the intended, suitable form, content, and behaviour would be.The Goal Directed Design (GDD) methodology is used in order to add customized guidelines and to embed the guidelines into the prototype.